Webinar Transformasi Organisasi melalui Budaya Organisasi - Nurwanti; Gulo, Yupiter; Tjahyanti, Setia; Sunny, Gloria Christina; Suhendra, M. Fariz Raihan Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Organizational transformation is crucial in a constantly changing era, but these efforts often fail because they overlook the vital role of organizational culture as the primary foundation. This webinar aims to provide an understanding of the importance of organizational culture through a conceptual approach from Dr. Nurwanti and a real-world case study from Mr. Yupiter Gulo, particularly in the transformation process of PT Kereta Api Indonesia (KAI). The information from the webinar shows that strengthening the organizational culture, such as implementing the AKHLAK values, is a key factor in achieving significant and sustainable change, as evidenced by KAI's improved performance. This article concludes that true transformation begins with a shift in values and mindset and serves as a guide for leaders in driving positive change.